Training And Education for Umkm Actors Related to Digital Marketing Strategies and Business Financial Management in Paropo Village, Panakukang District, Makassar City - Muhammad Chaerul; Nurmadhani Fitri Suyuthi; Syamsul Riyadi; Nur Alim Djalil; Yasmi Yasmi; Muh. Khairil Rusman; Risal Sepdiansar; Erni Tamsil; Alauddin Alauddin (Journal of Universal Community Empowerment Provision, 2025)
This community service activity aimed to improve the capacity of Micro, Small, and Medium Enterprises (MSMEs) in Paropo Village, Panakukang District, Makassar City, to face the challenges of the digital era. Training and education are focused on two main aspects: digital marketing strategies and business financial management. The implementation method included a participatory approach through interactive training sessions, simulations, group discussions, and direct mentoring. The results demonstrated an increase in participants' understanding and skills in using social media and other digital platforms for product promotion and marketing. Furthermore, participants gained practical knowledge in simple financial record keeping, cash flow management, and short- and long-term financial planning. Evaluation of the activity, conducted through pre- and post-tests, demonstrated significant improvements in participants' knowledge and skills. It is hoped that this activity will have a sustainable impact on the development of participants' businesses and strengthen the competitiveness of MSMEs in the region. This activity also opens up opportunities for further collaboration with the local government and related institutions in digital-based MSME development.